2019
DOI: 10.1111/hae.13860
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of plasma and platelet tissue factor pathway inhibitor, factor V and Protein S in people with haemophilia

Abstract: Introduction Tissue factor pathway inhibitor (TFPI) is a naturally occurring anticoagulant found in plasma, where it circulates bound to lipoproteins, factor V (FV) or Protein S (PS), and in platelets. Therapeutic agents targeting TFPI are under development for the treatment of haemophilia A and haemophilia B. Aim To begin to understand how TFPI, FV and PS interact to modulate haemophilia bleeding. Methods Plasma and platelet antigen concentrations of these factors were determined in 73 people with haemophilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In contrast, protein S levels were reduced both in plasma (33%) and in platelets (26%). 98 Prince and colleagues showed that blocking protein S anticoagulant functions in plasma of individuals with hemophilia normalized their thrombin generation in vitro. 97 Together, these findings suggest that the reduction in protein S levels helps partially rebalance their coagulation.…”
Section: Protein S In Hemos Tati C Reg Ul Ationmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, protein S levels were reduced both in plasma (33%) and in platelets (26%). 98 Prince and colleagues showed that blocking protein S anticoagulant functions in plasma of individuals with hemophilia normalized their thrombin generation in vitro. 97 Together, these findings suggest that the reduction in protein S levels helps partially rebalance their coagulation.…”
Section: Protein S In Hemos Tati C Reg Ul Ationmentioning
confidence: 99%
“…They showed that platelet TFPIα and FV levels were increased (21% and 50%, respectively) compared to healthy blood donors, while only minor differences were seen in plasma. In contrast, protein S levels were reduced both in plasma (33%) and in platelets (26%) 98 . Prince and colleagues showed that blocking protein S anticoagulant functions in plasma of individuals with hemophilia normalized their thrombin generation in vitro 97 .…”
Section: Protein S In Hemostatic Regulationmentioning
confidence: 99%
“…2,4,5 However, platelet TFPIα and FV concentrations do not correlate, which is consistent with their different locations within the platelet. 16,23 Here, we found that platelet TFPIα in two individuals with the FV east Texas variant was normal, indicating that FV-short does not alter platelet TFPIα, and implicating elevated plasma TFPIα as the cause of the bleeding disorder. Human platelet FV is adsorbed from plasma.…”
Section: Discussionmentioning
confidence: 65%
“…21,22 Platelet TFPIα does not localize to α-granules where FV is located, but instead appears to be in the cytoplasm. 22 The plasma concentrations of FV and TFPIα correlate 16,23 and increases in plasma FV-short greatly increase plasma TFPIα. 2,4,5 However, platelet TFPIα and FV concentrations do not correlate, which is consistent with their different locations within the platelet.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas one study's results indicate that haemophilia B patients have lower free TFPI levels than Haemophilia A patients, 14 other studies showed no significant difference in TFPI levels between patients with Haemophilia A and haemophilia B 15 . 30 Whereas in one of these studies 15 there was no difference between TFPI levels in haemophilia patients and healthy individuals, in the second study 30 a mild decrease in plasma TFPIα in haemophilia patients when compared to blood donors was observed. Nevertheless, there is lack of published information specifically on the TFPI levels in paediatric haemophilia subjects.…”
Section: Introductionmentioning
confidence: 97%